2020
DOI: 10.1002/adfm.201909260
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, Properties, and Applications of Bimetallic Nanoparticles of Noble Metals

Abstract: Bimetallic nanoparticles of noble metals are of high interest in imaging, biomedical devices, including nanomedicine, and heterogeneous catalysis. Synthesis, properties, characterization, biological properties, and practical applicability of nanoparticles on the basis of platinum group metals and the coin metals Ag and Au are discussed, also in comparison with the corresponding monometallic nanoparticles. In addition to the parameters that are required to characterize monometallic nanoparticles (mainly size, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
202
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(235 citation statements)
references
References 211 publications
3
202
0
Order By: Relevance
“…It is based on the use of oleylamine to solubilize and reduce the silver metallic precursor for the shell under annealing for a controlled time at the surface of the Au seed, which is itself synthesized by different pathways in an organic medium. The resulting Au@Ag core-shell NPs are of controlled crystallinity and composition; factors that play a fundamental role in their optical and catalytic properties [13,30,31]. Furthermore, they have a narrow size distribution that facilitates their 3D assembly after deposition on a solid substrate for further applications as new SERS platforms with tunable optical properties [32].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the use of oleylamine to solubilize and reduce the silver metallic precursor for the shell under annealing for a controlled time at the surface of the Au seed, which is itself synthesized by different pathways in an organic medium. The resulting Au@Ag core-shell NPs are of controlled crystallinity and composition; factors that play a fundamental role in their optical and catalytic properties [13,30,31]. Furthermore, they have a narrow size distribution that facilitates their 3D assembly after deposition on a solid substrate for further applications as new SERS platforms with tunable optical properties [32].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al prepared gold nanoparticles with a size of 2.5 nm by reducing the gold in the presence of glutathione with different ratios of gold to ligand and found different emission maxima for the resulting nanoparticles [54]. However, it must be stressed not all ultrasmall nanoparticles of noble metals show autofluorescence [55][56][57]. Gold nanoparticles and clusters are especially useful for this purpose.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic properties of bimetallic nanoparticles depend on the structures that are different between the core–shell structure and the disordered structure and composition of alloy nanoparticles. Pt–Ni alloy nanoparticles catalyze the oxygen reduction reaction ten times faster than Pt nanoparticle [ 200 ]. Another report showed that Pt–Ru alloy and Pt–Ru core–shell nanoparticles show differences in catalytic reactions [ 201 ].…”
Section: Properties Of Alloy Nanoparticlesmentioning
confidence: 99%